Pyridine-promoted dediazoniation of aryldiazonium tetrafluoroborates: Application to the synthesis of SF5-substituted phenylboronic esters and iodobenzenes - Iakobson, George; Du, Junyi; Slawin, Alexandra M. Z.; Beier, Petr (Beilstein Journal of Organic Chemistry, 2015)
Pyridine promotes dediazoniation of aryldiazonium tetrafluoroborates. The formed aryl radicals were trapped with B2pin2, iodine, or tetrahydrofuran to afford boronic esters, iodobenzenes and benzenes, respectively. The application to the synthesis of (pentafluorosulfanyl)phenylboronic esters, iodo(pentafluorosulfanyl)benzenes and (pentafluorosulfanyl)benzene is shown.
Keywords: borylation; diazonium salts; iodination; pyridine; sulfur pentafluorides